THE STATE OF INVESTMENT ACTIVITY IN UZBEKISTAN - Mukumova Nargis Nuriddinovna; Isrofilov Firdavs Ibroxim o'g'li (Scholar Express Journals, 2023)
This article describes the state and trends in the development of investment activities in the Republic of Uzbekistan. The regulatory and legal framework relating to investment activities is disclosed.
Keywords: Foreign investment; direct investment; investment activity; investor